Double Extrahepatic Portosystemic Shunt in a Bitch - Correction with the Use of Ameroid Constrictor Ring - Miyaguni Morais, Carolina Yumi; Cristina dos Santos, Victória; Konrad Nava Calva, Catherine; Vitória Hörbe, Anna; da Silva Reinstein, Rainer; Pereira Toscano, Cauê; Herreira Jarrouge, Daniel; Veloso Brun , Maurício (Acta Scientiae Veterinariae, 2024)
Background: Portosystemic shunts (PSS) are common vascular anomalies in dogs. There is a breed prevalence, with small dogs, particularly Yorkshire terriers, being more affected. PSS can be extrahepatic or intrahepatic, single or multiple, congenital or acquired, and can cause neurological, gastrointestinal, and urinary clinical signs. While clinical treatment is possible, surgical attenuation is known to significantly improve the quality of life for patients with PSS. This study aimed to report a case of a canine with two PSS that was surgically attenuated using an ameroid constrictor ring. Case: A 4-month-old unneutered bitch Yorkshire terrier weighing 3.3 kg was referred for treatment due to suspected ingestion of a copper wire. The physical examination revealed neurological signs and abdominal tenderness. Based on the patient's history and physical findings, copper intoxication was suspected, and PSS was considered a possible diagnosis. Lateral radiography showed contents in the stomach that appeared heterogeneous and contained radiopaque structures, indicating a gastric foreign body. The patient underwent exploratory celiotomy, which confirmed the suspicion and allowed for its removal by gastrostomy. During the post-operative period, the patient had a slow recovery from anesthesia and continued to display neurological signs. A CT scan revealed a 0.6 cm extrahepatic porto-azygos shunt and a 0.25 cm anomalous vessel originating from the porto-azygos shunt and inserted into the caudal vena cava and gastric vein branches. After diagnosis and stabilization of clinical signs, a 2nd exploratory celiotomy was performed to correct both PSS. The 1st larger anomalous vessel was corrected by implanting a 5 mm ameroid constrictor ring, while a 3.5 mm constrictor ring was implanted in the 2nd anomalous vessel. The patient remained stable post-surgery and was discharged 5 days later. At the 7-day follow-up, the patient was alert, with only occasional moments of agitation. Discussion: The present case reports the presence of double portosystemic shunt porto azygos with the presence of multiple gastric branches. Portoazygous PDs represent 25% of all congenital extrahepatic shunts diagnosed in dogs. Surgical attenuation is essential for reducing clinical signs and improving the quality of life for patients with PSS. A study of 128 dogs with congenital PSS, followed for 64 months, demonstrated that surgical intervention is directly associated with increased health-related quality of life scores. Portosystemic shunts are challenging vascular anomalies, both from a clinical and surgical point of view. In which, the management of the case involving clinical treatment to stabilize the patient linked to the surgical therapeutic maneuver is a determining factor for the success of the procedure. In this study, the surgical correction modality was ameroid constrictor ring implantation through celiotomy. The ameroid constrictor ring was the 1st gradual occlusion device to attenuate shunts. This technique has become more common for correcting congenital portosystemic shunts in dogs due to being safe and effectively promoting gradual shunt closure. It is the most beneficial therapy for patients with a higher success rate than other techniques, highlighting the constant evolution of veterinary medicine, with the ameroid constrictor ring being a notable milestone. In the present report, the surgical technique used, with the use of the ameroid constrictor ring, resulted in a satisfactory recovery of the patient presenting with a double portosystemic porto azygos shunt. Keywords: ameroid constrictor ring, portosystemic shunt, vascular anomaly Título: Duplo desvio portossistêmico extra-hepático em uma cadela - correção com a utilização de anel constritor ameróide Descritores: anomalia vascular, desvio portossistêmico, shunt, anel constrictor ameróide.